Elevated Red Cell Distribution Width to Platelet Ratio Is Associated With Poor Prognosis in Patients With Spontaneous, Deep-Seated Intracerebral Hemorrhage - Lehmann, Felix; Schenk, Lorena M.; Bernstock, Joshua D.; Bode, Christian; Borger, Valeri; Gessler, Florian A.; Güresir, Erdem; Hamed, Motaz; Potthoff, Anna-Laura; Putensen, Christian; Schneider, Matthias; Zimmermann, Julian; et al. (Frontiers in Neurology, 2021)
Object: Inflammatory response is an important determinant of subsequent brain injury after deep-seated intracerebral hemorrhage (ICH). The ratio of red blood cell (RBC) distribution width to platelet count (RPR) has been established as a new index to reflect the severity of inflammation. To the best of our knowledge, no association between RPR and prognosis after spontaneous ICH has yet been reported. Methods: In all patients with deep-seated ICH treated at our Neurovascular Center from 2014 to 2020, initial laboratory values were obtained to determine RPR in addition to patient characteristics and known risk factors. Subsequent multivariate analysis was performed to identify independent risk factors for 90-day mortality after deep-seated ICH. Results: Hundred and two patients with deep-seated ICH were identified and further analyzed. Patients with an initial RPR < 0.06 exhibited significantly lower mortality rate after 90 days than those with an initial RPR ≥ 0.06 (27 vs. 57%; p = 0.003). Multivariate analysis identified “ICH score ≥ 3” (p = 0.001), “anemia on admission” (p = 0.01), and “elevated RPR ≥ 0.06” (p = 0.03) as independent predictors of 90-day mortality. Conclusions: The present study constitutes the first attempt to demonstrate that the ratio of RBC distribution width to platelets—as an independent inflammatory marker—might serve for prognostic assessment in deep-seated ICH.